Practical guide to insulin therapy in type 2 diabetes mellitus (Tranining module for health care providers, 2010)
This Practical Guide to Insulin Therapy has been developed to provide a clear and concise approach to all health care providers on current concepts in the use of insulin in the management of type 2 diabetes (T2DM).